2017
DOI: 10.1038/leu.2017.344
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the genomic landscape of multiple myeloma highlights novel prognostic markers and disease subgroups

Abstract: In multiple myeloma, next generation sequencing (NGS) has expanded our knowledge of genomic lesions, and highlighted a dynamic and heterogeneous composition of the tumor. Here, we used NGS to characterize the genomic landscape of 418 multiple myeloma cases at diagnosis and correlate this with prognosis and classification. Translocations and copy number changes (CNAs) had a preponderant contribution over gene mutations in defining the genotype and prognosis of each case. Known and novel independent prognostic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 34 publications
2
63
0
Order By: Relevance
“…Interestingly, very few nonrecurring mutations or aneuploidies were found in proteasome subunit genes in our cohort, confirming their rarity. 16,55 We assessed high-risk genetic 3 ), double-hit events, 11 apolipoprotein B mRNA editing enzyme, catalytic polypeptide-like (APOBEC) signature contribution, 13 TP53 mutations, 9 and CRBN pathway mutations 15 and found that at least 1 such event was present in 65% of patients ( Figure 2D).…”
Section: Genomic Makeup Of Treatment-resistant Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, very few nonrecurring mutations or aneuploidies were found in proteasome subunit genes in our cohort, confirming their rarity. 16,55 We assessed high-risk genetic 3 ), double-hit events, 11 apolipoprotein B mRNA editing enzyme, catalytic polypeptide-like (APOBEC) signature contribution, 13 TP53 mutations, 9 and CRBN pathway mutations 15 and found that at least 1 such event was present in 65% of patients ( Figure 2D).…”
Section: Genomic Makeup Of Treatment-resistant Samplesmentioning
confidence: 99%
“…PRDM1 is a crucial transcription factor in plasma cells and its mutations-deletions have been observed as late events in MM development, 64 with a possible prognostic role, even at diagnosis. 9 We had data on pomalidomide-based salvage treatment of 14 patients. Of these, 4 showed primary refractoriness, including 3 with loss of chr13 and del(17p).…”
Section: Survival Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…These subtypes vary in chemosensitivity and survival, suggesting that although patients share a common histological and clinical phenotype, the underlying biology is distinctly heterogeneous. Preliminary studies have suggested that these patterns exist in MM as well 5,7,912 , but have not yet been systematically defined in large cohorts with broad sequencing coverage.…”
mentioning
confidence: 99%
“…More than 40 genetic lesions were druggable but only 3 of them are already targeted in the clinical practice [159]. Although there are new therapeutic approaches for patients with high-risk MM [23,24] and the introduction of active treatments with different mechanisms of action compared to chemotherapy, therapy-sensitive patients have a very variable duration of response [93]. The MM natural history is characterized by further recurrences of diseases whose response to treatments is not durable.…”
Section: Future Perspectivesmentioning
confidence: 99%